2002
DOI: 10.1021/ja017520u
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Binding of Cadmium(II), Mercury(II), and Arsenic(III) to the de Novo Designed Peptides TRI L12C and TRI L16C

Abstract: Designed alpha-helical peptides of the TRI family with a general sequence Ac-G(LKALEEK)(4)G-CONH(2) were used as model systems for the study of metal-protein interactions. Variants containing cysteine residues in positions 12 (TRI L12C) and 16 (TRI L16C) were used for the metal binding studies. Cd(II) binding was investigated, and the results were compared with previous and current work on Hg(II) and As(III) binding. The metal peptide assemblies were studied with the use of UV, CD, EXAFS, (113)Cd NMR, and (111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
207
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(238 citation statements)
references
References 66 publications
29
207
0
2
Order By: Relevance
“…By changing the leucine layer above the metal to alanine to allow better water access above the metalbinding site, we designed a peptide (TRI L12AL16C) that binds Cd(II) solely in a four-coordinate geometry, with three cysteinyl thiolates and one exogenous water. This observation would suggest that Cd(II) binds to these peptides as the exo conformer, consistent with the longer Cd(II)-S distances (2.54 Å), which are more reminiscent of Pb(II) than As(III) (8). These observations make one consider whether metalloregulatory proteins may be able to differentiate different toxic metals in part by their preference for endo [As(III)] versus exo [Pb(II)/Cd(II)] binding.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…By changing the leucine layer above the metal to alanine to allow better water access above the metalbinding site, we designed a peptide (TRI L12AL16C) that binds Cd(II) solely in a four-coordinate geometry, with three cysteinyl thiolates and one exogenous water. This observation would suggest that Cd(II) binds to these peptides as the exo conformer, consistent with the longer Cd(II)-S distances (2.54 Å), which are more reminiscent of Pb(II) than As(III) (8). These observations make one consider whether metalloregulatory proteins may be able to differentiate different toxic metals in part by their preference for endo [As(III)] versus exo [Pb(II)/Cd(II)] binding.…”
Section: Discussionmentioning
confidence: 56%
“…Previously, we have shown that the three-stranded coiled coil TRI peptides [Ac-G(L a K b A c L d E e E f K g ) 4 G-NH 2 ] designed with the heptad repeat strategy, such as TRI L16C (sequences of all peptides are in Table 1), were able to model the unusual trigonal thiolate Hg(II) coordination geometry seen in the MerR metalloregulatory protein (7). We have also examined the binding of the heavy metals Cd(II), Pb(II), and Bi(III) to the TRI peptides to better understand their modes of toxicity (8,9). Based on this success, we examined whether the trigonal thiolate metal-binding cavities of TRI derivatives would be good models of the active site of ArsR.…”
mentioning
confidence: 99%
“…PAC Spectroscopy. PAC spectroscopy and sample preparation were performed as described (35,36); however, a typing error of ''10 -40 mL'' should be ''10 -40 L,'' and the current experiment with 111m Cd and TRIL12LDL16C was carried out in a 1:12 ratio, at pH 9.1, 1°C, and in 55% wt/wt sucrose to further reduce the Brownian tumbling of the molecules. Finally, all fits were carried out with 300 data points, disregarding the 5 first points due to systematic errors in these.…”
Section: Methodsmentioning
confidence: 99%
“…The simplest way is to analyze protein scaffolds empirically and introduce cysteine-rich coordination sites. Several α-helical coiled-coil metalloproteins capable of binding Co(II), Fe(II), Zn(II), Cd(II), Hg(II), and As(II) have been designed this way (Matzapetakis et al, 2002;Petros et al, 2006). More complex coordination sites were engineered with the aid of computational searching, for example, the Cys 2 -His 2 zinc binding sites and Fe 4 -S 4 sites (Lu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%